CK1δ/ε inhibition induces ULK1-mediated autophagy in tumorigenesis - Vivian Weiwen Xue; Shanshan Liu; Qi Sun; Jiong Ning; Huan Li; Weilan Wang; Sapna Sayed; Xibao Zhao; Li Fu; Desheng Lu (Translational Oncology, 2024)
Introduction: Autophagy is an important mechanism of cell homeostasis maintenance. As essential serine/threonine-protein kinases, casein kinase I family members affect tumorigenesis by regulating a variety of cellular progression. However, the mechanism by which they regulate autophagy remains unclear. Materials and methods: We silenced CK1δ/ε in cancer cells and observed cell morphology, the expression of autophagy-related genes, and its impact on cancer cell growth and viability. By inhibiting CK1δ/ε-induced upregulation of autophagy genes, we profiled the regulatory mechanism of CK1δ/ε on autophagy and cancer cell growth. The impact of CK1δ/ε inhibition on tumor cell growth was also assessed in vivo. Results: Here, we found that CK1δ/ε played an important role in ULK1-mediated autophagy regulation in both lung cancer and melanoma cells. Mechanically, silencing CK1δ/ε increased ULK1 expression with enhanced autophagic flux and suppressed cancer cell proliferation, while ULK1 knockdown blocked the activation of autophagy caused by CK1δ/ε inhibition. By silencing CK1δ/ε in syngeneic mouse model bearing LLC1 murine lung cancer cells in vivo, we observed tumor growth suppression mediated by CK1δ/ε inhibition. Conclusion: Our results provide evidence for the role of CK1δ/ε in the regulation of tumorigenesis via the ULK1-mediated autophagy, and also suggest the impact of CK1δ/ε inhibition on tumor growth and its significance as a potential therapeutic target.